Interpreting Degree Semantics - Wellwood, Alexis (Frontiers in Psychology, 2020)
Contemporary research in compositional, truth-conditional semantics often takes judgments of the relative unacceptability of certain phrasal combinations as evidence for lexical semantics. For example, observing that "completely full" sounds perfectly natural whereas "completely tall" doesn’t has been used to motivate a distinction whereby the lexical entry for "full" but not for "tall" specifies a scalar endpoint. So far, such inferences seem unobjectionable. In general, however, applying this methodology can lead to dubious conclusions. For example, observing that "slightly bent" is natural but "slightly cheap" is not (that is, not without a 'too cheap' interpretation) leads researchers to suggest that the interpretation of bent involves a scalar minimum but cheap does not, contra intuition—after all, one would think that what is minimally cheap is (just) free. Such claims, found in sufficient abundance, raise the question of how we can support semantic theories that posit properties of entities that those entities appear to lack. This paper argues, using theories of adjectival scale structure as a test case, that the (un)acceptability data recruited in semantic explanations reveals properties of a two- stage system of semantic interpretation which can support divergences between our semantic and metaphysical intuitions.